کامطالعاتی جائزہMuhammad The Prophet of Revolutionمولانا وحید الدین خان اور اسکی کتاب : Study Review of Mulana Waheed ud din khan and his book’’Muhammad ﷺ the Prophet of Revolution’’ - Dr. Attaullah; Furqan , Muhammad; Sabir , Muhammad (International Research Journal of Arabic and Islamic Studies, 2024)
After independence, the principle and view of objectivity in biography came out with a new dimension, as a result of which, along with the movement and revolutionary trend, the invitational and reformist tendency in biography increased as well as the public tendency. The way in which the mentioned tendencies of biography after independence highlighted the purpose and importance of biography can be considered as an achievement of biography.In the research under study, its methods, styles and subjects have been evaluated by taking the award-winning English book fo Al-Sirat-ul-Nabawiyyah as a basis. The biography of Muhammad (صلی اللہ علیہ وسلم) is an art form. A biography consists of the events, situations, sayings and actions of any person. But biographers and other scholars have divided the work of biography into different terms by naming it as an art, as if the biographers have derived the art from the habits, actions and good sermons of the Prophet.